Pengaturan Mengenai Pendaftaran Pendirian Firma Pada Sistem Administrasi Badan Usaha - Permadi, I Made Hengki (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 3 (2019)DO - 10.24843/AC.2019.v04.i03.p12, 2019)
The process or procedure for establishing a firm is regulated in Article 22 and Article 23 of the Commercial Law Code (hereinafter referred to as KUHD). In this provision, it is stipulated that the firm must be established with an authentic deed and registered with the Registrar of the District Court where the firm was established. The regulations in the KUHD are not in line with the Minister of Law and Human Rights Regulation Number 17 Year 2018 regarding the Registration of the Military Alliance, the Fima Alliance and the Civil Alliance which indicates that the registration of the firm is carried out in the Legal Entity Administration System (hereinafter referred to as SABU). it appears that there is a norm conflict between the two rules. This study aims to determine the arrangements in registering the Firm and the legal consequences of not registering the Firm in the Business Entity Administration System (SABU). This research is a normative legal research. In research using a statutory and conceptual approach. Using primary and secondary legal materials. The results showed that based on the principle of Lex Superiori derogate Legi Inferiori, based on the hierarchy of statutory regulations, the KUHD which is equivalent to the Law is stronger than the Regulation of the Minister of Law and Human Rights Number 17 of 2018 concerning Registration of Komanditer Alliance, Firm Alliance and Civil Alliance whose position is under Government Regulations and Presidential Regulations, because the Acts are higher than Government Regulations and Presidential Regulations. The legal consequence of not registering a firm with SABU is that the name of the firm can be used first by other firms so it must change the name of the firm concerned with another name because in the SABU system there is a registration of the firm's alliance name. If there is a partnership with another firm that registers the name of the firm first, then the name of the same firm cannot be registered again and the firm is deemed invalid. Proses atau tata cara pendirian firma diatur dalam Pasal 22 dan Pasal 23 Kitab Undang-Undang Hukum Dagang (yang selanjutnya disebut KUHD). Dalam ketentuan tersebuti menentukan bahwa firma harus didirikan dengan akta otentik dan didaftarkan pada Kepaniteraan Pengadilan Negeri dimana firma tersebut didirikan. Peraturan dalam KUHD tersebut tidak sejalan dengan Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 17 Tahun 2018 tentang Pendaftaran Persekutuan Komanditer, Persekutuan Fima dan Persekutuan Perdata yang mengisyaratkan bahwa pendaftaran firma dilakukan pada Sistem Administrasi Badan Hukum (yang selanjutnya disebut SABU). terlihat bahwa adanya konflik norma diantara kedua aturan itu. Penelitian ini bertujuan untuk mengetahui   pengaturan dalam pendaftaran Firma  dan akibat hukum apabila tidak mendaftarkan Firma pada Sistem Administrasi Badan Usaha (SABU). Penelitian ini merupakan penelitian hukum normatif. Dalam penelitian menggunakan pendekatan perundang-undangan dan konseptual. Menggunakan bahan hukum primer dan sekunder.   Hasil penelitian  menunjukkan  bahwa  berdasarkan asas Lex Superiori derogate Legi Inferiori maka berdasarkan hirarki peraturan perundang-undangan, KUHD yang setara dengan Undang-Undang lebih kuat dibanding Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 17 Tahun 2018 tentang Pendaftaran Persekutuan Komanditer, Persekutuan Firma dan Persekutuan Perdata yang kedudukannya dibawah Peraturan Pemerintah dan Peraturan Presiden, karena Undang-Undang kedudukannya lebih tinggi dari Peraturan Pemerintah dan Peraturan Presiden. Akibat hukum dari tidak didaftarkannya firma pada SABU, yaitu nama firma dapat dipakai terlebih dahulu oleh firma lainnya sehingga harus mengganti nama firma yang bersangkutan dengan nama yang lain karena di dalam sistem SABU terdapat pendaftaran nama persekutuan firma. Jika ada persekutuan firma lain yang mendaftarkan nama firmanya terlebih dahulu maka nama firma yang sama tidak akan bisa didaftarkan kembali dan firma tersebut dianggap tidak sah pendiriannya.